102 wacky monster jokes - Pellowski, Michael ([Mahwah, N.J.] : Watermill Press, 1992)
A collection of riddles about monsters, including "What do monsters like on their mashed potatoes? Grave-y."
Keywords: Wit and humor, Juvenile; Monsters -- Juvenile humor; Monsters -- Wit and humor; Riddles